Solar assisted multiple-effect evaporator. (20th January 2017) - Sharan, Prashant; Bandyopadhyay, Santanu
Abstract: Multiple-effect evaporator (MEE) is used for concentrating the liquor. A substantial energy saving can be achieved by integrating MEE with a thermo-vapor compressor (TVC). TVC is a device in which the low-pressure vapor produced from MEE is compressed with the help of the high-pressure motive steam supplied externally, to produce a medium pressure vapor. This medium pressure vapor acts as a heat source for MEE. The high-pressure motive steam can be produced from concentrating solar thermal system, which is a renewable and non-polluting source of energy. The present study deals with the integration of linear Fresnel reflector (LFR) with MEE-TVC system. The objective of the present work is to minimize the total annual cost for the integrated MEE-TVC and LFR system. The important parameters affecting the annual cost for the integrated system are solar design radiation and temperature of the motive steam. A methodology is developed to determine the optimal solar radiation and steam temperature. The proposed methodology is demonstrated through a case study for manufacturing of corn glucose. The annual cost for the system is 87, 106 /y, with optimal steam temperature 250 °C and optimal design radiation 600 W/m 2 . Sensitivity analysis is also carried out for the selection of the optimal operating parameters. The cost of the auxiliary heating source plays a dominating factor on the economic feasibility of the integrated system. Highlights: Integration of solar thermal system with multiple-effect evaporator. Cost minimization of integrated system by optimization of operating parameters. Role of auxiliary heating source on economic feasibility of the integrated system. Beak even price for solar thermal collector.